Changes in treatment and outcome of oesophageal cancer in Denmark between 2004 and 2013. Issue 10 (18th July 2017) - Kjaer, D W; Larsson, H; Svendsen, L B; Jensen, L S
Abstract: Background: Since 2003, care for patients with oesophageal cancer has been centralized in a few dedicated centres in Denmark. The aim of this study was to assess changes in the treatment and outcome of patients registered in a nationwide database. Methods: All patients diagnosed with oesophageal cancer or cancer of the gastro-oesophageal junction who underwent oesophagectomy in Denmark between 2004 and 2013, and who were registered in the Danish clinical database of carcinomas in the oesophagus, gastro-oesophageal junction and stomach (DECV database) were included. Quality-of-care indicators, including number of lymph nodes removed, anastomotic leak rate, 30- and 90-day mortality, and 2- and 5-year overall survival, were assessed. To compare quality-of-care indicators over time, the relative risk (RR) was calculated using a multivariable log binomial regression model. Results: Some 6178 patients were included, of whom 1728 underwent oesophagectomy. The overall number of patients with 15 or more lymph nodes in the resection specimen increased from 38·1 per cent in 2004 to 88·7 per cent in 2013. The anastomotic leak rate decreased from 14·8 to 7·6 per cent (RR 0·66, 95 per cent c.i. 0·43 to 1·01). The 30-day mortality rate decreased from 4·5 to 1·7 per cent (RR 0·51, 0·22 to 1·15) and the 90-day mortality rate from 11·0 to 2·9 per cent (RR 0·46, 0·26 to 0·82). There were no statistically significant changes in 2- or 5-year survival rates over time. Conclusion: Indicators of quality of care have improved since the centralization of oesophageal cancer treatment in Denmark. Abstract : Better short-term outcome